2018
DOI: 10.2991/ijcis.2018.25905181
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Detection of Routing Attacks in the Internet of Things

Abstract: Cyber threats are a showstopper for Internet of Things (IoT) has recently been used at an industrial scale. Network layer attacks on IoT can cause significant disruptions and loss of information. Among such attacks, routing attacks are especially hard to defend against because of the ad-hoc nature of IoT systems and resource constraints of IoT devices. Hence, an efficient approach for detecting and predicting IoT attacks is needed. Systems confidentiality, integrity and availability depends on continuous secur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 34 publications
0
84
0
Order By: Relevance
“…A deep-learning established machine learning method has been presented in [14] for the IoT to detect the routing attacks. The Cooja IoT emulator has been employed to generate high-fidelity attack data within IoT networks having 10 to 1000 nodes.…”
Section: Related Workmentioning
confidence: 99%
“…A deep-learning established machine learning method has been presented in [14] for the IoT to detect the routing attacks. The Cooja IoT emulator has been employed to generate high-fidelity attack data within IoT networks having 10 to 1000 nodes.…”
Section: Related Workmentioning
confidence: 99%
“…It also increases the accuracy of the model to 98.59% which is better than other state-of-the-art models. In [506], a DNN based scalable routing attack detection framework is proposed where the attack dataset is extracted from the Cooja IoT simulator. The proposed framework preprocess the extracted simulator data and selects the useful features which is fed into DNN model as input.…”
Section: A Deep Learning In Intrusion Detectionmentioning
confidence: 99%
“…In this paper [16] authors has analyzed the behavior of the routing attacks like black-hole, clone attack, civil, sinkhole attack, and selective forwarding attacks and concluded that due to this attack the network may damage in terms of network throughput the experimental results was shown by using the netsim2. In this paper [17] proposed an deep learning approach to detect the routing attacks in the internet of things to simulating the proposed system contiki cooja to simulator was used. Here the proposed system will detect the routing attacks like hello flood, version number modification attack and decreased rank attack.…”
Section: Figure 3 : Rpl Protocol In Iot Networkmentioning
confidence: 99%